2014
DOI: 10.1111/ceo.12398
|View full text |Cite
|
Sign up to set email alerts
|

Cambridge community Optometry Glaucoma Scheme

Abstract: The COGS community-based glaucoma screening programme is a safe and effective way of evaluating glaucoma referrals in the community and reducing false-positive referrals for glaucoma into the hospital system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 27 publications
3
76
0
Order By: Relevance
“…The present study identified a potential clinical pathway for patients with suspected angle closure spectrum disease, where the majority of patients do not require onward ophthalmological assessment. The overall proportion of all patients who could be discharged back into the community for ongoing optometric care (20.1 per cent) was similar to some previous reports and was lower than others . Specifically with regard to patients referred for angle assessment, gonioscopic findings were not once noted in the referral letter, indicating a gap in current community optometry that is addressed in the present model.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The present study identified a potential clinical pathway for patients with suspected angle closure spectrum disease, where the majority of patients do not require onward ophthalmological assessment. The overall proportion of all patients who could be discharged back into the community for ongoing optometric care (20.1 per cent) was similar to some previous reports and was lower than others . Specifically with regard to patients referred for angle assessment, gonioscopic findings were not once noted in the referral letter, indicating a gap in current community optometry that is addressed in the present model.…”
Section: Discussionsupporting
confidence: 79%
“…The present study evaluated the effect of a new, recently activated referral pathway on improving triaging effectiveness and patient outcomes for angle closure spectrum disease. This pathway was put in place after noting that other existing glaucoma‐specific patient pathways do not necessarily regard angle closure spectrum disease as a distinct entity requiring a separate triage process. In doing so, this study sought to evaluate potential reasons for pathway utilisation in order to guide further improvements to the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early detection and prompt treatment of glaucoma and ocular hypertension may prevent or significantly delay glaucoma‐related visual disability, leading to a better quality of life among affected persons and reduced both direct and indirect costs to the society . Opportunistic cases finding by community‐based optometrists accounted for more than 90% of all glaucoma referrals in the United Kingdom, while office‐based opportunistic screening has been proposed as a feasible model in the United States . In Australia, a hybrid model of collaborative care for glaucoma patients and suspects between ophthalmologists and optometrists have been proposed .…”
Section: Discussionmentioning
confidence: 99%
“…12 No diagnoses of glaucoma were missed suggesting that although inaccuracies and disagreements exist, virtual assessment is a safe adjunct in glaucoma care. 13 A further example of community-based management of retinal diseases is the monitoring of retinal diseases, an incidental finding on routine fundal examination, which may be associated with an increased risk of choroidal melanoma.…”
mentioning
confidence: 99%